Block Copolymer Micelles with an Intermediate Star‐/Flower‐Like Structure Studied by 1H NMR Relaxometry. Issue 9 (28th March 2014) - Weiss, Jan; Wienk, Hans; Boelens, Rolf; Laschewsky, André
<x xml:space="preserve">Abstract</x> 1H NMR relaxation is used to study the self‐assembly of a double thermoresponsive diblock copolymer in dilute aqueous solution. Above the first transition temperature, at which aggregation into micellar structures is observed, the trimethylsilyl (TMS)‐labeled end group attached to the shell‐forming block shows a biphasic T2 relaxation. The slow contribution reflects the TMS groups located at the periphery of the hydrophilic shell, in agreement with a star‐like micelle. The fast T2 contribution corresponds to the TMS groups, which fold back toward the hydrophobic core, reflecting a flower‐like micelle. These results confirm the formation of block copolymer micelles of an intermediate nature (i.e., of partial flower‐like and star‐like character), in which a part of the TMS end groups folds back to the core due to hydrophobic interactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>